Evolução dos Insetos-Praga na Cultura da Soja no Mato Grosso - Wiest, Aleson; Barreto, Marliton Rocha (EntomoBrasilis, 2012)
O presente trabalho apresenta o desenvolvimento da cultura da soja no estado de Mato Grosso quanto aos insetos-praga associados a essa cultura. Constatou-se que em 1978 essa cultura apresentava seis espécies-pragas principais e nenhuma praga secundária ou esporádica. No ano de 2008, 33 espécies são consideradas insetos-pragas nesta cultura, sendo 10 espécies consideradas pragas principais, 11 espécies secundárias e 12 espécies esporádicas. Esses dados demonstram um aumento superior a 450% quanto à incidência de pragas da cultura da soja, no período 1978 - 2008, no estado do Mato Grosso, sendo que as pragas principais tiveram um aumento de 66,67%. Evolution of Insect Pests in Soybeans in Mato Grosso Abstract. This study presents the development of soy crops in the state of Mato Grosso regarding the pest-insects that have been associated to that culture. It was found that in 1978 soybean crops had six main pest-species and no secondary or sporadic pests. In 2008, 33 species were considered to be pest-insects to this culture, 10 of which are classified as main pests, 11 as secondary, and 12 as sporadic pests. These data show an increase of over 450% in the incidence of soybean crop pests from 1978 - 2008, in the state of Mato Grosso, with a 66.67% increase in main pests.